Cxcr4 regulation of interneuron migration is disrupted in 22q11.2 deletion syndrome - Meechan, Daniel W. (National Academy of Sciences, 2012)
Interneurons are thought to be a primary pathogenic target for several behavioral disorders that arise during development, including schizophrenia and autism. It is not known, however, whether genetic lesions associated with these diseases disrupt established molecular mechanisms of interneuron development. We found that diminished 22q11.2 gene dosage—the primary genetic lesion in 22q11.2 deletion syndrome (22q11.2 DS)—specifically compromises the distribution of early-generated parvalbumin-expressing interneurons in the Large Deletion (LgDel) 22q11.2DS mouse model. This change reflects cell-autonomous disruption of interneuron migration caused by altered expression of the cytokine C-X-C chemokine receptor type 4 (Cxcr4), an established regulator of this process. Cxcr4 is specifically reduced in LgDel migrating interneurons, and genetic analysis confirms that diminished Cxcr4 alters interneuron migration in LgDel mice. Thus, diminished 22q11.2 gene dosage disrupts cortical circuit development by modifying a critical molecular signaling pathway via Cxcr4 that regulates cortical interneuron migration and placement.